2015
DOI: 10.1542/peds.2015-1669
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal Versus Infant Vitamin D Supplementation During Lactation: A Randomized Controlled Trial

Abstract: OBJECTIVE: Compare effectiveness of maternal vitamin D 3 supplementation with 6400 IU per day alone to maternal and infant supplementation with 400 IU per day.METHODS: Exclusively lactating women living in Charleston, SC, or Rochester, NY, at 4 to 6 weeks postpartum were randomized to either 400, 2400, or 6400 IU vitamin D 3 /day for 6 months. Breastfeeding infants in 400 IU group received oral 400 IU vitamin D 3 /day; infants in 2400 and 6400 IU groups received 0 IU/day (placebo). Vitamin D deficiency was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
192
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(201 citation statements)
references
References 53 publications
6
192
0
3
Order By: Relevance
“…With the reported low content of dietary vitamin D in the traditional Nepalese diet (33), UVB radiation and breast milk are by far the most important sources of vitamin D in young children. Exclusive breast-feeding has been considered inadequate to prevent vitamin D deficiency (13,34), but recent reports show that vitamin D content in human milk is highly dependent on the mother's vitamin D status (35,36). Local sun-exposure habits associated with breast-feeding in Nepal, such as outdoor breast-feeding (12) and the tradition of sunbathing infants younger than 3 months (37), may therefore be plausible explanations for the relatively high plasma 25(OH)D concentration found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…With the reported low content of dietary vitamin D in the traditional Nepalese diet (33), UVB radiation and breast milk are by far the most important sources of vitamin D in young children. Exclusive breast-feeding has been considered inadequate to prevent vitamin D deficiency (13,34), but recent reports show that vitamin D content in human milk is highly dependent on the mother's vitamin D status (35,36). Local sun-exposure habits associated with breast-feeding in Nepal, such as outdoor breast-feeding (12) and the tradition of sunbathing infants younger than 3 months (37), may therefore be plausible explanations for the relatively high plasma 25(OH)D concentration found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Skin pigmentation reduces UVB penetration into epidermis by ~90% thereby limiting the production of previtamin D3 by the skin [23]. A recent study indicated that infants may get enough vitamin D from breast milk if their mothers take high-dose vitamin D supplements [25]. The complementary foods in the diets of Indian infants and children are primarily cereal based with less vitamin D [26].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, 25.3% of deaths in children aged 1-59 months in India were due to pneumonia, totaling 150,169 deaths [10]. Globally, diarrhea causes 9% of under-5 deaths, most of these in developing countries [10].…”
Section: Introductionmentioning
confidence: 99%
“…D kiekis, vidutiniškai 5-80 IU/l. Kūdikio, kuris yra išimtinai žindomas motinos, per dieną gaunančios apie 400 IU vitamino D, kalcidiolio koncentracija kraujyje būna mažesnė nei norma (< 12,5 mmol/l) [16]. Autorių nuomone, motinos pieno ir kūdikio vitamino D stoka susijusi su nepakankamu motinų buvimu saulėje, o tai ypač aktualu mūsų klimato juostos motinoms, pagimdžiusioms rudens-žiemos laikotarpiu [7,16,17].…”
Section: Brandus Pienasunclassified